MITIGATING DHCP STARVATION ATTACK USING SNOOPING TECHNIQUE - Nuhu, Abdulhafiz A.; Echobu, Faith O.; Olanrewaju, Oyenike M. (FUDMA JOURNAL OF SCIENCES, 2020)
Over the years, devices and the use of networks has grown by leaps and bounds thereby making the Dynamic Host Configuration Protocol (DHCP) a very important network management tool. Initially, the protocol focused more on ease of use rather than security, which made it vulnerable to attacks like DHCP starvation among others. There are techniques which have been developed over the years to mitigate attacks to the DHCP server. This research used DHCP snooping to mitigate the attack to achieve a more secured network. The experiment was done in a virtual environment using GNS3. Due to the type of malicious packets that was generated during attack, the LAN was isolated from the Internet to avoid any destruction. The experiment demonstrated how easy it was to attack and exhaust DHCP pool of address thereby prohibited the legitimate client from getting IP address. The research also demonstrated the mitigation of DHCP starvation attack by using DHCP snooping.
Keywords: DHCP, DHCP Starvation Attack, DHCP Snooping, GNS3